Fuzzy logic‐based intelligent frequency and voltage stability control system for standalone microgrid. (22nd December 2017) - Asghar, Furqan; Talha, Muhammad; Kim, Sung Ho
Summary: The increasing penetration of renewable energy resources in power systems has improved microgrid's implementation. A microgrid is a localized grouping of electricity sources and loads that normally operates connected to and synchronous with the traditional centralized grid but can disconnect and function autonomously as physical and economic conditions dictate. Main factors to control in a microgrid are mainly frequency and voltage regulation, energy management, operation, and control scheme. This high penetration of renewable generation systems with their intermittent nature and unpredictable output power fluctuations might cause many control problems and large frequency/voltage deviation in microgrid stand‐alone operation. Thus, to maintain the microgrid stability, an efficient and highly reliable control scheme is required. In this paper, a newly proposed fuzzy logic‐based robust control mechanism is used to stabilize the frequency and direct current bus voltages in large fluctuations caused by sudden changes in power generation or load side. Also, supercapacitor and battery energy storage system are used to stabilize direct current bus voltages. This proposed method ensures the system efficiency and stability by reducing the system complexity and transient time, minimizing the frequency deviations, and preventing synchronous generator units from surpassing their power ratings in response to these disruptions. Simulation results also validate the effectiveness of the proposed controller in comparison with previous techniques.